Low-dose carbon monoxide inhalation to increase total hemoglobin mass and endurance performance: scientific evidence and implications - Gatterer, Hannes; Dünnwald, Tobias; Woyke, Simon; Faulhaber, Martin; Schumacher, Yorck Olaf; Schobersberger, Wolfgang (Frontiers in Physiology, 2024)
Recently, chronic intermittent inhalation of low-dose carbon monoxide (CO) has been postulated as a practice to increase total hemoglobin mass with potential beneficial effects on endurance performance. In this perspective article, we discuss the potential performance enhancing capabilities as well as the safety concerns, which include individual variability in CO response, and acute and chronic health effects. It is also important to note that according to the World-Anti-Doping-Agency (WADA), carbon monoxideCO inhalation could fall under "M1. Manipulation of Blood and Blood Components" and therefore could be is consideredlassified as a prohibited method ifby the World-Anti-Doping-Agency (WADA) when used as a non-diagnostic tool.